E-commerce Service Chatbot Application Design using KNN and Random Forest Methods - Fardan Zamakhsyari (JISKA (Jurnal Informatika Sunan Kalijaga))
Our lives are profoundly shaped by technology, with the expansion of e-commerce being a notable outcome that demands attention. Given the prevalence of smartphones equipped with rapid messaging and networking applications, individuals often utilize these platforms to communicate with sellers, offering a convenient means for sellers to efficiently engage with a diverse customer base. Recognizing this trend, there arises a necessity for the digital transformation of services to enhance operational efficiency. In response to this need, the researcher has developed a chatbot application aimed at improving customer service, employing machine learning techniques with the KNN and Random Forest algorithms. To assess the application's viability, the chatbot's results undergo an accuracy test, revealing a satisfactory accuracy value of 71.4%, thereby affirming its feasibility.